Tokophobia and fear of birth: a workshop consensus statement on current issues and recommendations for future research. (1st January 2021) - Jomeen, J.; Martin, C. R.; Jones, C.; Marshall, C.; Ayers, S.; Burt, K.; Frodsham, L.; Horsch, A.; Midwinter, D.; O'Connell, M.; Shakespeare, J.; Sheen, K.; et al.
ABSTRACT: Objective : To discuss and develop a statement on the current state of the evidence and opinion in Fear of Childbirth (FoC) and Tokophobia (Tocophobia), and to provide recommendations. Background : A group met in 2019 to discuss the state of clinical and academic knowledge relating to FoC/Tokophobia. Five key areas were agreed as the focus of the meeting. Methods : 12 internationally acknowledged experts, in this or a closely related area (e.g. PTSD) met to discuss their understanding of the evidence for FoC/ Tokophobia and current practice. The consensus described in this paper constitutes the expression of the general opinion of the participants and does not necessarily imply unanimity. Keys points : Work focussed on tokophobia is recent and there remains a wide range of issues, which were addressed in the workshop including complexity in defining prevalence, a theoretical lack of understanding, which creates challenge for robust assessment and the identification of risk factors. An improved aetiological and developmental understanding of the tokophobia is required to underpin appropriate, effective and evidence-based interventions. Evaluation of pathways of care and relevant interventions, should be a focus of future research. Conclusion : Significant gaps remain within the FoC/tokophobia knowledge base. Further research is necessary.